PEMANFAATAN FORUM KOMUNIKASI KOMITE SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN SMA DI KABUPATEN GOWA - Mustakim Mustakim; Muhammad Farid (KAREBA : Jurnal Ilmu Komunikasi, 2013)
Abstrak Peranan dan fungsi forum komunikasi komite sekolah dalam peningkatan mutu pendidikan SMA. Penelitian ini bertujuan mengetahui gambaran pelaksanaan forum komunikasi komite sekolah dan sekolah di SMA Kabupaten Gowa, gambaran mutu pendidikan SMA di Kabupaten Gowa, gambaran keterkaitan antara peran dan fungsi forum komunikasi komite sekolah dengan mutu pendidikan SMA di Kabupaten Gowa. Metode penelitian ini adalah deskriptif kualitatif. Hasil penelitian menunjukkan bahwa pemanfaatan forum komunikasi komite sekolah dalam peningkatan mutu pendidikan SMA di Kabupaten Gowa telah berjalan dengan baik. Dengan adanya kegiatan forum rapat yang dilaksanakan baik secara rutin maupun insidental di kalangan pengurus forum komunikasi komite sekolah, pengurus pimpinan forum komunikasi komite sekolah, pengurus forum komunikasi komite sekolah dengan pimpinan sekolah dan rapat kordinasi pimpinan forum komunikasi komite sekolah dengan pihak sekolah, sehingga peran dan fungsi forum komunikasi komite sekolah sebagai pemberi pertimbangan, pendukung, pengontrol, dan mediator berdampak positif dalam peningkatkan mutu pendidikan melalui input, proses dan output pendidikan.Abstract The role and functions of school committees communication forum in improving the quality of high school education. This study aimed to overview the implementation of the school committee and a forum for communication in high school Gowa, the picture quality of high school education in Gowa, picture of the relationship between the roles and functions of school committees communication forum with the quality of high school education in Gowa. This research method is descriptive qualitative. The results showed that the use of a communication forum of the school committee in improving the quality of high school education in Gowa has been going well. With the meeting of the forum held both routine and incidental communication among school committee forum administrators, board of school committee leadership communication forum, board communication forum with the school committee and the school leadership coordination meeting of the school committee leadership communication forum with the school, so that the role and forum functions as a conduit of communication school committee consideration, support, control, and mediators have a positive impact in enhancing the quality of education through the input, process and output of education.